Pengaruh Penggunaan Youtube Terhadap Minat Belajar Mahasiswa PBA UIN Sultan Aji Muhammad Idris Samarinda Angkatan 2021 - Haykal, Muhammad; Latifah, Nor; Nurdiniyah, Syti Qoirunisa'; Wardhana, Kautsar Eka (Borneo Journal of Language and Education, 2021)
This journal reviews the influence of the use of Youtube on the learning interest of PBA UINSI students in the class of 2021. This study aims to determine whether Youtube affects the learning interest of PBA UINSI Samarinda students. This type of research is classified as quantitative research. The research instrument is filling out a questionnaire / questionnaire. The data source of this research is filling out a questionnaire then proceed with analyzing the data statistically to determine the effect of using Youtube on the learning interest of PBA UINSI Samarinda students class of 2021. The benefit of this research is that it can find out the development of science in the field of technology as information and reference material for the development of science, especially in the field of technology and is also very useful for students who are not very good at understanding lessons through teachers, they can learn on their own through other learning media, one of which is Youtube. Quantitative research methods were used in this study. The research was conducted in November 2021 at the Sultan Aji Muhammad Idris Samarinda State Islamic University. This research is classified as survey research, which uses a questionnaire / questionnaire as an instrument. As for this study using Arabic Language Education students class of 2021 as a population of 77 people. While the sample of this study used 20 respondents using random sampling technique. Based on hypothesis testing on the ANOVA test, the result is 1.00> 0.05 then variable X is linear to variable Y and Ha is accepted.